PENINGKATAN HASIL BELAJAR SISWA SEKOLAH DASAR MELALUI BELAJAR KOOPERATIF TIPE JIGSAW - Elmia Umar (Jurnal Inovasi, 2011)
The objective of this research is to know the learning process to increase elementary student outcomes in social science study through the cooperative learning and whether there was an increase after the act. About twenty students of school Laboratories, State University of Gorontalo are the subject this research. The research uses action research method Kemmis & Mc.Taggart. Data collecting technique uses interview, documentation and observation. This research also uses descriptive analysis. The result of the research describes that the cooperative learning in social science study of elementary school gives impact for increasing social science learning. The result of the test showed that the increased in average eighty five percent and the result. In observation showed eighty percent from the total number of student who get a good assessment